SUSTAINABILITAS KETAHANAN PANGAN MELALUI PEMBERDAYAAN KELEMBAGAAN EKONOMI DESA (BUMDES TIGALUNGGUNG DESA LINGGAJATI) - Unang Unang; Edy Suroso; Riantin Hikmahwidi; Zulfikar Noormansyah (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
The availability of sufficient food for households will be greatly influenced by household income to access to meet their family needs. Therefore, in the long term food security will remain vulnerable if the economic condition of the family is still a problem.In accordance with the theme of Internal Community Service at Siliwangi University 2020, namely food security, it is necessary to take a more comprehensive and long-term approach, namely through intervention in the management of economic institutions in Linggajati village, namely BUMDes Tigalunggung in Linggajati Village, Sukaratu District, Tasikmalaya Regency. Intervention programs that have been carried out are through dialogue, mentoring and equipment assistance. The results of the dialogue concluded that there must be a restructuring of the organization according to the needs and an inventory of economic potential must be carried out and prioritize which can be managed according to the capabilities of the BUMDes. Assistance is carried out through counseling on BUMDes philosophy, Bumdes Management, standardization and marketing of products managed by BUMDes Tigalunggung, Business Planning through the Canvas Business Model (BMC) and financial management / accounting assistance. Dry coffee picking equipment was provided. Through this approach, it is hoped that the efforts of the people of Linggajati Village will be more productive, effective and competitive. Furthermore, it will ensure long-term community food security